EFEKTIVITAS PEMBELAJARAN DI LUAR KELAS (OUTDOOR LEARNING) DENGAN PENDEKATAN PMRI PADA MATERI SPLDV - Rohim, Abdur; Asmana, Arezqi Tunggal (Jurnal Pembelajaran Matematika, 2018)
Abstract: In learning process, teachers often ignore students’ initial knowledge. Students are not given the opportunity to rediscover and construct their own mathematics ideas. Classroom learning activities are often boring. It can affect students' learning motivation. The low learning motivation of students towards mathematics subject influences students’ learning outcomes. For this reason, learning innovation is a crucial matter. PMRI approach is offered as a solution which learning process is done outside the classroom with a game, learning that links mathematics material with everyday life context, and learning that views students as active participants. The purpose of this study is to describe the effectiveness of outdoor learning with PMRI approach in SPLDV material. The subjects in this study are students of class VIII-C of State Junior High School (SMPN) 4 Lamongan and teachers who carried out learning. It is descriptive research with one shot case study design. The results reveal that the teachers’ ability in managing learning with PMRI approach is effective, because each observed aspect is included in good/very good category. Students’ activities during learning process with PMRI approach are effective because every aspect of students’ activity is categorized in the range of effectiveness. Students' classical learning completeness is good, which is shown by 83% of students fulfilling KKM. So, it can be concluded that outdoor learning with PMRI approach in SPLDV material is effective..Keywords: Effectiveness, Outdoor Learning, PMRI, SPLDV.